A colonização das razões políticas pelo discurso religioso: um exercício crítico à teocracia da política dos costumes - JESUS, Michael Lima de (2018)
The present work consists of the study of the colonization of political reasons by religious discourse, done through a critical exercise in the theocracy of the politics of customs, when analyzing the parliamentary position of the Evangelical Front of the National Congress (Evangelical Bancada) in its apparent theocratic ideology in search for a civil society that is driven by Christian foundations. In order to do this, several methodological procedures were used during the course of the work, being this analysis and intense bibliographical research, documentary analysis of the draft laws, opinions issued, pronouncements, lawsuit and activity in bills (as well as the political posture-juridic) of the National Parliamentary Congress (Evangelical Parliamentary Front), with respect to those that deal with the sexuality content, from the 52nd term (2003-2006), the stage of its establishment. The method used in this study is dialectical-deductive. The methodology adopted is an analytical study through a technical procedure of data collection and weightings related to such study, therefore, positions and decisions related to each sphere of the study. Finally, in consideration of the interpretations and inferences obtained by the analysis and research carried out, as well as through dialectical analysis, the Evangelical Parliamentary Front of the National Congress (Evangelical Bancada) was considered as having no adequacy to the Christian theological discourse, as well as not belonging to the philosophical-political tradition of conservatism.